Impact of an Interprofessional Training Session on Student Spirituality and Faith Integration in the Workplace - Felisha L Younkin; Emily Laswell; Kristi Coe; Joy Hanson; Robert Snyder; Aleda Chen (Health for All Nations, 2019)
Providing spiritual care to patients can result in improved health outcomes and health-related quality of life. However, healthcare professionals feel largely unprepared to address spiritual health. The objective of this study was to determine the impact of an interprofessional training session on student spiritual health and perceived confidence and competence in sharing their faith with patients. An all-day, interprofessional workshop to assist students in assessing their own spiritual health, identifying opportunities to address patient spiritual health, and sharing their faith ethically was incorporated. Nursing, pharmacy, allied health/kinesiology, psychology, and pre-med students attended and completed assessments related to the student outcomes pre-workshop, post-workshop, and at 3, 6, and 9 months post-workshop. Significant improvements in perceived confidence and competence were documented initially and longitudinally. Baseline student spiritual health was high; only participation in Christian activities significantly improved in the assessment of their spiritual health. Further study is necessary to fully understand the impact of this training on student spiritual health. Nonetheless, incorporation of this training can better prepare students to engage in spiritual care of patients and share their own faith with others ethically as opportunities arise.